2022
DOI: 10.3390/membranes12020244
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Sodium Separation by a Lithium Composite Membrane Used in Electrodialysis Process: Concept Validation

Abstract: The recent expansion of global Lithium Ion Battery (LIBs) production has generated a significant stress on the lithium demand. One of the means to produce this element is its extraction from different aqueous sources (salars, geothermal water etc.). However, the presence of other mono- and divalent cations makes this extraction relatively complex. Herein, we propose lithium-sodium separation by an electrodialysis (ED) process using a Lithium Composite Membrane (LCM), whose effectiveness was previously demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…The application of this LCM5 on electrodialysis was tested using two ED cells: a two-compartment and a four-compartment cell [ 77 ]. The second one was found to be advantageous thanks to its membrane-protection ability, presented in Figure 3 .…”
Section: Main Results Obtained During the Period 2012–2022mentioning
confidence: 99%
See 1 more Smart Citation
“…The application of this LCM5 on electrodialysis was tested using two ED cells: a two-compartment and a four-compartment cell [ 77 ]. The second one was found to be advantageous thanks to its membrane-protection ability, presented in Figure 3 .…”
Section: Main Results Obtained During the Period 2012–2022mentioning
confidence: 99%
“… Schematic illustration and operating principle of our four-compartment ED cell. Adapted from [ 77 ]. …”
Section: Figures Scheme and Tablesmentioning
confidence: 99%
“…Mass balance of metals showed that 48.4 wt % of Li from the anolyte was recovered in the form of Li 2 CO 3 dried product. A recent literature on membrane-based Li separation and recovery reports Li recoveries in that range of 5.9–99%, but this information only accounts for the Li reported in the catholyte and not as a final solid product. ,, Nevertheless, improvements in Li 2 CO 3 yields are necessary in order to make this technology industrially relevant. Due to the OER and MnO 2 formation, the pH of the anolyte decreased from 2.10 to 1.28, while the pH of the catholyte increased from 8.15 to 9.92.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, 6 Li isotope separation factor was not calculated in the above-mentioned paper and further studies are needed. Furthermore, the lithium solid ceramics can be used to separate lithium ions from sodium and potassium, and Ounissi et al used lithium composite membrane to separate lithium from sodium ions [29] with electrodialysis, but the selectivity coefficient of Li + over Na + was recorded to 112.3, a value which is higher than the selectivity coefficients previously reported in other electrodialysis methodologies [30]. Nevertheless, cation-exchange resins methods are usually preferred as preconcentration steps employed for the separation of lithium from other alkaline ions.…”
Section: Challenges In Development Of Separation Methods For Lithium ...mentioning
confidence: 99%